Translation as interpretation: a hermeneutical inquiry into the semantics of the scriptural language - Solihu, Abdul Kabir Hussain (s.n, 2012)
Translation makes mutual understanding possible across diverse cultures and localities. There are different theories of translation each aspiring to objectively represent the original text. Language is a sine qua non of translation and thus the philosophy of translation is inextricable linked to the philosophy of language. The force of language as a carrier or maker of meaning and medium of understanding is well recognised in the field of semantics and hermeneutics. The proposed study aims to examine the role of language and culture and their relationship in meaning making